Factores bio-socio-culturales y el dolor en pacientes con pancreatitis. Hospital Victor Lazarte Echegaray - Carranza Rodríguez, Clara Elisa (2019)
The present research work of descriptive correlational type; whose objective was to determine the bio-socio-cultural factors and the pain of the patient with pancreatitis in the emergency service of Víctor Lazarte Echegaray Hospital, the population was made up of a total of 50 patients who attended the emergency service to whom he applied an instrument on bio-socio-cultural factors and a graph to measure pain. To measure the correlation between both variables, the Chi square test was applied, reaching the following conclusion: a. 60% of the patients were older than 35 years, 26% were between the ages of 20 and 35, and only 14% were younger than 20 years old. 60% corresponded to the male sex and 38% to the female sex. Regarding the degree of instruction 44% with higher education, 36% with complete secondary, 14% with primary and only 6% without instruction. In what corresponds to the occupation, 28% are workers, 26% with independent work, 24% are employees and 22% are professionals. b. The degree of pain found was 52% at the high level, 28% at the medium level and 20% the low level and c. A significant relationship was found between the factors of age, sex and educational level with the pain of the patient with pancreatitis.